Fanaticism Reflected by Cath Avery’s Character in The Novel Fangirl - Ade Amalia; Novi Rusnarty Usu; Farid Muhamad (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study examines fanaticism as reflected in the characters of Rainbow Rowell’s novel Fangirl, focusing on fanatical behavior and its underlying factors. Using a psychological approach to literary analysis, the study applies theories of fanaticism along with Freud’s motivation theory, to analyze the mental and emotional processes of the characters, particularly Cath Avery as a devoted fan of Simon Snow. The analysis reveals that fanaticism in the novel is characterized by obsessive attachment, emotional investment, and actions driven by an idealized perception of fictional narratives. Psychological needs such as escapism, validation, and identity formation significantly contribute to this behavior, while subconscious desires and past experiences further shape the characters’ deep devotion. These findings offer insights into the psychological foundations of fanaticism in literature, illustrating how fictional works influence individual behavior and motivation. This study enhances the understanding of the intersection between psychology and literature, emphasizing how literary characters reflect real-life psychological tendencies.